Socioeconomic determinants of banking margins how do they play a role? - Dvořák, Michal; Brůna, Karel, 1973-; Jakl, Jakub; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2013)
This thesis reveals and describes channels through which socio-economic factors affect bank interest margins. This is done by inspection of state-of-the-art banking firm and dealership models and extensive surveying of empirical literature. 5 particular channels are discussed. 1) Uncertainty associated with costs and benefits of switching the provider of banking services, amplified by the customer risk aversion. 2) Ability of banks to deter switching by various ways, for example by low transparency of rate books or installing direct financial costs when switching. 3) Authorities' willingness to rescue troubled banks, leading to less precautionary behavior of banks. 4) Shareholders' risk aversion, leading to more or less ambitious return-on-equity targets, which in turn affect risk behavior of management. 5) Size of banks implied by anti-merger regulation and low country population impacting margins through economies to scale. Proxies for all these determinants are outlined to enable econometric investigation in further research. In the modeling part, it is shown that dealership models inappropriately price credit risk. Moreover, alterative treatment which increases the importance of operating costs is suggested. Finally, a brand new "satisficer" framework in which management maximizes the likelihood of reaching a benchmark is presented. Such model is both more realistic and general than all its predecessors. It allows their reconciliation and allows for investigation of more margin determinants.
Vedoucí práce: Karel Brůna
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: bankovnictví a pojišťovnictví [obor dipl. práce]; diplomové práce; master's theses